Análise da relação entre o EVA®, indicadores de desempenho e o preço da ação: um estudo de caso - Piveta, Fernando (2006)
With the managerial models evolution, the companies have been found, incessantly, ways to minimize the risk inherent for taking decision. New evaluation methodologies are persistently live inside of the organizations, for example, the EVA®, providing an updated evaluation between investments and its costs, promoting a value generation overview. The aim of this dissertation is to promote a theoretical and practical evaluation among EVA®, performance indicators and stock price in a study of case contemplating Embraer and the worldwide aerospace market. However, this dissertation begins with a theoretical observation of the main themes in analysis, as capital structure, costs involved and EVA®, and forward, applying these concepts in the EVA® observation as value methodology and its correlation with other performance indicators, as well as Embraer and world aerospace market. The results achieved in this research, at first moment by Embraer followed by aerospace sector, were similar didn t have significant correlation between EVA® and stock price. Similarly, the more significant correlations occurred between EVA® and the operational performance indicators, reflecting the current positions of the companies in analysis